EFFECT OF CARRYING CAPABILITIES OF CORN PLANT LANDON THE INCOME OF CORN FARMERS IN MOPU VILLAGE, BUKAL DISTRICT BUOL REGENCY - M, Rosita; Ramlawaty, Ramlawaty; Aqfir, Aqfir (International Journal of Economic Entrepreneurship and Business Management, 2024)
This research aims to determine the effect of the carrying capacity of corn plantations on the income of corn farmers in Mopu Village, Bukal District, Buol Regency. This research uses a quantitative associative method. The data source is primary data obtained through questionnaires and documentation related to this research. The data analysis technique uses statistical calculations using the SPSB 16 application. The results of the research show that the carrying capacity of land has a significant influence on the income of corn farmers in Mopu Village, Bukal District, Buol Regency.